Measurement of the t¯t production cross section in the τ þ jets final state in pp collisions at ffiffi s p = 8 TeV using the ATLAS detector - Aaboud, M. (2017)
A measurement of the inclusive pp → t¯t þ X production cross section in the τ þ jets final state using only the hadronic decays of the τ lepton is presented. The measurement is performed using 20.2 fb−1 of proton-proton collision data recorded at a center-of-mass energy of ffiffi s p ¼ 8 TeV with the ATLAS detector at the Large Hadron Collider. The cross section is measured via a counting experiment by imposing a set of selection criteria on the identification and kinematic variables of the reconstructed particles and jets, and on event kinematic variables and characteristics. The production cross section is measured to be σt¯t ¼ 239 29 pb, which is in agreement with the measurements in other final states and the theoretical predictions at this center-of-mass energy.